Peran Konseling Kelompok dengan Teknik Sosiodrama dalam Mengatasi Perilaku Prososial pada Remaja di Kelurahan 8 Ilir Palembang - Yusuf Pratama; Abdur Razzaq; Lena Merianti (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research is entitled The Role of Group Counseling Using Sociodrama Techniques in Overcoming Prosocial Behavior in Adolescents in Subdistrict 8 Ilir Palembang. The aim of this research is to determine the description of prosocial behavior of adolescents before being given sociodrama techniques and to determine the role of group counseling using sociodrama techniques in dealing with prosocial behavior of adolescents. The research method used is field research. Data collection techniques include observation, interviews and documentation. Data analysis techniques consist of data reduction, data presentation and drawing conclusions. The results of the research are first, teenagers in sub-district 8 Ilir had low prosocial behavior before being given sociodrama techniques. This was proven by the results of the pre-action interview where it was seen that teenagers from sub-district 8 Ilir Palembang had low prosocial behavior, where in each indicator in the interview items, teenagers from sub-district 8 Ilir answered questions quite indifferently. Second, group counseling using sociodrama techniques has a significant role in overcoming prosocial behavior of teenagers in the 8 Ilir sub-district. This behavior increased significantly along with the meeting when the behavior was given. This is in line with the enthusiasm of the teenagers at every service delivery meeting, as well as the answers to every discussion regarding what should be done in the climax of the drama script. Apart from that, the interview answers to each indicator of prosocial behavior also gave a positive response, which could also be the answer that group counseling using sociodrama techniques has a significant role in overcoming adolescent prosocial behavior.